2024
DOI: 10.1039/d4nj00473f
|View full text |Cite
|
Sign up to set email alerts
|

Amination of polylactic acid to alanine using a Ru–Co bimetallic catalyst

Meng Cui,
Guyue Liu,
Cankun Ma
et al.

Abstract: The preparation of alanine from waste polylactic acid (PLA) is not only an effective way to recycle waste plastics, but also of great significance to develop a green, clean and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The time–course profile revealed that the yield of alanine acid rose almost linearly from 18.4 to 66.7% as the reaction time was extended from 1 to 10 h, while other byproducts, such as ammonium lactate and lactamide, decreased from 73.8 to 31.6% and 7.1 to 6.4%, respectively (Figure b). This suggests that ammonium lactate and lactamide should serve as the key intermediates in the amination of PLA to alanine . However, during the subsequent 8 h, the yield of alanine showed a slight increase from 66.7 to 76.1%, suggesting that the yield of alanine reached a plateau after an initial rapid increase.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The time–course profile revealed that the yield of alanine acid rose almost linearly from 18.4 to 66.7% as the reaction time was extended from 1 to 10 h, while other byproducts, such as ammonium lactate and lactamide, decreased from 73.8 to 31.6% and 7.1 to 6.4%, respectively (Figure b). This suggests that ammonium lactate and lactamide should serve as the key intermediates in the amination of PLA to alanine . However, during the subsequent 8 h, the yield of alanine showed a slight increase from 66.7 to 76.1%, suggesting that the yield of alanine reached a plateau after an initial rapid increase.…”
Section: Resultsmentioning
confidence: 98%
“…This suggests that ammonium lactate and lactamide should serve as the key intermediates in the amination of PLA to alanine. 13 However, during the subsequent 8 h, the yield of alanine showed a slight increase from 66.7 to 76.1%, suggesting that the yield of alanine reached a plateau after an initial rapid increase. Additionally, prolonging the reaction time beyond 18 h resulted in a gradual increase in the alanine yield.…”
Section: ■ Introductionmentioning
confidence: 91%
See 3 more Smart Citations